2023
DOI: 10.3847/1538-4357/ace2c4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Origin of the Absorption-line Variability in the Narrow-line Seyfert 1 Galaxy WPVS 007

Kaylie S. Green,
Sarah C. Gallagher,
Karen M. Leighly
et al.

Abstract: Broad absorption line quasars are actively accreting supermassive black holes that have strong outflows characterized by broad absorption lines in their rest-UV spectra. Variability in these absorption lines occurs over months to years depending on the source. WPVS 007, a low-redshift, low-luminosity narrow-line Seyfert 1 (NLS1) shows strong variability over shorter timescales, providing a unique opportunity to study the driving mechanism behind this variability that may mimic longer-scale variability in much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…We found that the data did not require a less restrictive model with multiple velocity-resolved ionization parameters. In order to calculate the total column density, we first calculated column density values corrected for the covering fraction from each bin and summed the values ( Arav et al 2005;Leighly et al 2018;Choi et al 2020;Green et al 2023). Similarly, the wind energetics, such as mass outflow rate, momentum flux, and kinetic luminosity, for the BAL were computed from the sum of the values calculated for each top-hat bin.…”
Section: A1 Best-fit Simbal Modelmentioning
confidence: 99%
“…We found that the data did not require a less restrictive model with multiple velocity-resolved ionization parameters. In order to calculate the total column density, we first calculated column density values corrected for the covering fraction from each bin and summed the values ( Arav et al 2005;Leighly et al 2018;Choi et al 2020;Green et al 2023). Similarly, the wind energetics, such as mass outflow rate, momentum flux, and kinetic luminosity, for the BAL were computed from the sum of the values calculated for each top-hat bin.…”
Section: A1 Best-fit Simbal Modelmentioning
confidence: 99%
“…Crucial information about the physical state of these outflows and their origin can be drawn from the study of their variations with time (Lundgren et al 2007;Gibson et al 2008Gibson et al , 2010Filiz Ak et al 2012;Capellupo et al 2011Capellupo et al , 2012Vivek et al 2014; Filiz ⋆ Based on observations collected at Southern African Large Telescope (SALT; Programme IDs 2015-1-SCI-005, 2018-1-SCI-009, 2019-1-SCI-019 and 2020-1-SCI-011) and the European Organisation for Astronomical Research in the Southern Hemisphere under ESO programme 093.A-0255. † E-mail: aromal@iucaa.in (PA) Ak et al 2013;McGraw et al 2017;Rogerson et al 2018;De Cicco et al 2018;Aromal et al 2022;Green et al 2023).…”
Section: Introductionmentioning
confidence: 99%